Pengaruh Beban Kerja terhadap Kinerja Pegawai pada Unit Pelaksana Teknis Daerah (UPTD) Puskesmas Batu-Batu Kabupaten Soppeng - Adelfi Islami; Uhud Darmawan Natsir; Burhanuddin; Romansyah Sahabuddin; Agung Widhi Kurniawan (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine how the influence of workload on the performance of employees at the Regional Technical Implementation Unit (UPTD) of the Health Center Batu-Batu Soppeng Regency. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study with a sample of 35 people. Data analyzed using a simple linear regression analysis method with assistance SPSS 23 data processing to prove the hypothesis. The research results show that the workload variable has a significant level of 0.000, which is more smaller than 0.05. The coefficient value is -0.416 which shows the influence given is negative to the dependent variable. This means that Ha is accepted and Ho is rejected so it can be said that workload has a negative effect and significant to employee performance.